Osgood-Schlatter disease in young athletes - Ciechanowska, Katarzyna (Journal of Education, Health and Sport, 2019)
Avascular necrosis constitute a syndrome characterized by the withering away of bone tissue and cartilaginous tissue without the participation of pathogenic microorganisms. This disease often occurs in the roots of the growing bones of children and young people and is a consequence of the lack of connection between vessels and the metaphyseal bone epiphysis (lack of collateral circulation) during growth. The aim of this article is to review the literature on the characteristics of Osgood-Schlater disease, its etiology, diagnosis and physiotherapy.